Pemanfaatan Umbi Uwi Dan Umbi Gadung SebagaiAlternatif Media Potato Dextrose Agar (Pda) UntukPertumbuhan Jamur - PRATIWI, RATNA SARI; , Triastuti Rahayu, S.Si, M.Si (2016)
Potato Dextrose Agar (PDA) is a common medium for mold growth. Media using potatoes as a carbohydrate source that is processed to produce instant PDA. In addition to potatoes, other tubers also has a high carbohydrate content such as uwi tubers and gadung tubers. This study aims to determine the growth of Aspergillus niger in media uwi tuber and gadung tuber as substitution of alternative media PDA medium for fungus growth. This study was an experimental study using a completely randomized design (CRD) of the factors, namely the type of media. The media type that is PDA (M0), uwi tubers media (M1), gadung tubers media (M2). Aspergillus niger fungus using the test of agar block method and incubated for 72 hours at a temperature of 280 C. Parameter research is the increase in diameter of the colony and sporulation Aspergillus niger by using data analysis techniques qualitative and quantitative descriptive. The results showed that Aspergillus niger experiencing the increase in diameter and sporulation by order of the best growth on PDA amounted to 48.3 mm with heavy sporulation then uwi tubers and gadung tuber 38.3 mm 31.8 mm thin with sporulation. Based on the results of the study concluded that the uwi tubers and gadung tubers can be used as an alternative media substitution PDA for fungus growth.